Deiksis dalam Film Bumi dan Manusia Karya Hanung Bramantyo - Azaa Izzatul Laila; Ahmad Firdaus; Zahra Nurainnisa Suhendar; Winda Dwi Hudhana; Asep Purwo Yudi Utomo (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
Deixis is a pragmatic study that examines the relationship between the structure of language and the environment in which the language is used. The phenomenon of deixis or use is most often seen in everyday conversation in the form of verbal language. Deixis is also found in the conversation of characters or figures in literary works such as films. The study entitled "Deixis in the Film Bumi dan Manusia by Hanung Bramantyo" examines the use of deixis in the film directed by Hanung Bramantyo with the title "Earth and Man". Persona, time, place, social, and discourse deixis are the five categories of deixis studied in this study. Researchers used analytical methods in the form of pragmatics with qualitative techniques to analyze the data that had been collected. The data used in this study include fragments of speech from film conversations, both words and phrases containing deixis, including personal deixis, time deixis, location deixis, social deixis, and discourse deixis. Watching movies, capturing data, recognizing, categorizing, analyzing, formulating, and presenting data are the stages of analyzing in this research. Data analysis illustrates that the film directed by Hanung Bramantyo with the title "Bumi dan Manusia" has a deixis in the form of person, time, place, social, and discourse.